1-7 Pengembangan Energi dan Penerangan Alternatif Biogas di Desa Margamukti, Pangalengan - Rafika Ratik Srimurni (ABDITEK NUSANTARA, 2020)
Margamukti Village is one of the villages located in the northern part of Bandung Regency, precisely in Pangalengan District. This village has great potential in the agricultural and livestock sectors. The population of Margamukti Village in 2017 was 17,437 people with a total of 5,273 Heads of Families (KK). Of this population, 3,078 people are farmers and 1,069 livestock businesses, meaning that 70.5% of the population of Margamukti Village depend on agriculture and animal husbandry for their livelihood. Margamukti Village is one of the villages that has started to initiate the use of renewable energy by using biogas from cow dung. Biogas is an alternative fuel for the future because it can be used as vehicle fuel and to generate electricity, including to meet household energy needs. The data collection method used in this PkM report is a descriptive method which includes: Observations were carried out by direct research into the area to identify community conditions, natural conditions, and people's daily activities. Activities with interviews regarding this matter, we conducted direct interviews with the Village Head, Head of RW, Community Leaders and Livestock Owners who have installed the biogas system. This community service focuses on optimal utilization of cow dung to be treated as waste and to manage the gas that comes out into a fire that is distributed. Distribution via PVC pipe to the gas stove. Also, through the channel, it is channeled to the lamp cover shirt which can be ignited with a lighter so that it lights up like a petromax lamp.Keywords: biogas, cow dung, lamp, stove